2013
DOI: 10.1530/eje-12-0532
|View full text |Cite
|
Sign up to set email alerts
|

Generalized glucocorticoid resistance caused by a novel two-nucleotide deletion in the hormone-binding domain of the glucocorticoid receptor gene NR3C1

Abstract: Objective: Generalized glucocorticoid resistance is characterized by impaired cortisol signaling, resulting from mutations of the glucocorticoid receptor (GR) gene NR3C1. The objective of our study was to identify the causative mutation in a patient with clinical manifestations compatible with generalized glucocorticoid resistance and to determine the functional consequences of the mutation. The possible occurrence of NR3C1 mutations in a selected group of hypertensive subjects with low plasma renin and aldost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Nr3c1 can both function as a transcription factor that binds to glucocorticoid response elements in the promoters of glucocorticoid responsive genes to activate their transcription or act as a regulator of other transcription factors. Nr3c1 mutations manifest as generalized glucocorticoid resistance (Donner et al , ), characterized by the insensitivity of target tissues to glucocorticoids, resulting in the compensatory activation of the HPA axis and CRH hypersecretion into the systemic circulation. Thus, secretagogin may be the first molecular hinge linking Nr3c1‐mediated feedback to CRH release from parvocellular neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Nr3c1 can both function as a transcription factor that binds to glucocorticoid response elements in the promoters of glucocorticoid responsive genes to activate their transcription or act as a regulator of other transcription factors. Nr3c1 mutations manifest as generalized glucocorticoid resistance (Donner et al , ), characterized by the insensitivity of target tissues to glucocorticoids, resulting in the compensatory activation of the HPA axis and CRH hypersecretion into the systemic circulation. Thus, secretagogin may be the first molecular hinge linking Nr3c1‐mediated feedback to CRH release from parvocellular neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Cereblon (CRBN) was recently identified as being essential for the anti-MM activity of IMiDs. [11][12][13][14][15][16][17][18] To date, the reported incidence of mutations in proteasome subunits, the CRBN pathway, or the steroid receptor is low, and mutations in these genes, except in single case studies 19,20 or in vitro cell line analyses, 20,21 have not yet been identified as a major source of primary or acquired drug resistance in larger MM data sets.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, loss of NR3C1 gene is associated with glucocorticoid resistance, which is a key component of childhood ALL therapy. Besides, deletion of NR3C1 gene is rare in B-ALL and significantly associated with clinical high risk of relapse and an inferior outcome, where it correlated to high rate of induction failure and death (2,7,29).…”
Section: Discussionmentioning
confidence: 99%